INCREASING THE PHYSICAL DEVELOPMENT INDICATORS OF SCHOOLCHILDREN WITH THE HELP OF LIGHT AND ATHLETICS EXERCISES (Scientific journal of the Fergana State University, 2023)
In order to improve the process of physical education, monitoring of the results of a study conducted by questionnaire methods is carried out on the implementation of various exercises related to athletics, the formation and development of their physical capabilities during the training sessions of a contingent of teachers. given in the article. The analysis of changes in indicators of the level of physical fitness and physical development of schoolchildren during the experiment is highlighted.